Pure Gold-Green Sweat Bee Augochlora pura (Say 1837) (Insecta: Hymenoptera: Halictidae: Halictinae) - Clancy A. Short; Andrea Lucky (EDIS)
Includes: Introduction - Synonymy - Distribution - Description - Life Cycle - Biology- Management - Natural Enemies - Selected References